Relevansi Pendidikan Multikultural dalam Perspektif Filsafat Pendidikan Islam (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2025)
This study aims to analyze the meaning of multicultural education from the perspective of Islamic educational philosophy and its relevance to the development of education in Indonesia. This research uses a qualitative approach with a literature study method. The process of collecting literature is carried out through several scientific databases such as Google Scholar and DOAJ, as well as through academic books, proceedings, and relevant national and international journal articles. The analysis stage is conducted using content analysis techniques, which involves analyzing the meanings, concepts, and relationships between ideas that emerge in various literatures. The analysis results indicate that multicultural education is an educational approach that emphasizes recognition, appreciation, and acceptance of cultural, ethnic, and religious diversity. From the perspective of Islamic educational philosophy, values such as justice, equality, tolerance, and respect for human beings are in line with the concept of multiculturalism. Integrating these values into Islamic education has the potential to strengthen social harmony, build inclusive student character, and prevent conflicts arising from differences in identity. This study concludes that the implementation of multicultural education within the framework of Islamic education is highly relevant for creating a peaceful, just, and human-oriented society. The study emphasizes the need to revitalize the curriculum and pedagogy of Islamic education to be more responsive to the diverse realities of Indonesian society